2017
DOI: 10.4172/2155-6148.1000800
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided TAP Block with or without Dexmedetomidine vs. Local Infiltration of the Wound after Open Herniorrhaphy: A Randomized Prospective Controlled Study

Abstract: Objectives: Transversus abdominis plane (TAP) block and local anesthetic wound infiltration (LAI) can provide a variable effective pain relief at the wound site after surgery. This prospective study was designed to evaluate the postoperative analgesic efficacy of TAP with or without dexmedetomidine compared with LAI of the wound after herniorrhaphy. Materials and methods:Sixty adult patients were divided into 3 groups of 20 patients each. Group1 (TAPD): Patients received single shot ultrasound-guided (US) TAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Secondary pain-related outcomes were all significantly reduced with the exception of rest pain score at 24 postoperative hours, dynamic pain score at 12 postoperative hours, and intravenous morphine consumption at 2 postoperative hours (Table 2). One study reported zero incidence of postoperative haematoma and visceral injury 20 . The incidence of postoperative infection or local anaesthetic systemic toxicity was not reported by any study, and neither was duration of hospital stay.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Secondary pain-related outcomes were all significantly reduced with the exception of rest pain score at 24 postoperative hours, dynamic pain score at 12 postoperative hours, and intravenous morphine consumption at 2 postoperative hours (Table 2). One study reported zero incidence of postoperative haematoma and visceral injury 20 . The incidence of postoperative infection or local anaesthetic systemic toxicity was not reported by any study, and neither was duration of hospital stay.…”
Section: Resultsmentioning
confidence: 88%
“…24 Five studies included patients undergoing inguinal hernia repair only, [18][19][20]22,24 while two included patients undergoing inguinal or infra-umbilical hernia repair, 21,23 without presenting data for surgical subgroups. Inguinal or infra-umbilical hernia repair was performed with an open surgical approach in five studies 18,20,21,23,24 and with laparoscopy in two studies. 19,22 All interventions were performed under general anaesthesia and maintained with inhalation agents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Ultrasound guided TAP block produces good pain relief and reduces intraoperative and postoperative opioid requirement. 7,8 TAP block duration is limited to the effect of administered local anaesthetics, so to prolong the duration of block adjuvants are added, and dexmedetomidine is a good choice. Dexmedetomidine is a highly selective alpha 2 adrenergic receptor agonist, ten times more selective than clonidine.…”
Section: S C Us S I O Nmentioning
confidence: 99%